Bond-Slip Models for FPR-Concrete Interfaces Subjected to Moisture Conditions. (18th January 2017) - Shrestha, Justin; Zhang, Dawei; Ueda, Tamon
Abstract : Environmental related durability issues have been of great concerns in the structures strengthened with the fiber reinforced polymers (FRPs). In marine environment, moisture is one of the dominant factors that adversely affect the material properties and the bond interfaces. Several short-term and long-term laboratory experimental investigations have been conducted to study such behaviors but, still, there are insufficient constitutive bond models which could incorporate moisture exposure conditions. This paper proposed a very simple approach in determining the nonlinear bond-slip models for the FRP-concrete interface considering the effect of moisture conditions. The proposed models are based on the strain results of the experimental investigation conducted by the authors using 6 different commercial FRP systems exposed to the moisture conditions for the maximum period of 18 months. The exposure effect in the moisture conditions seems to have great dependency on the FRP system. Based on the contrasting differences in the results under moisture conditions, separate bond-slip models have been proposed for the wet-layup FRP and prefabricated FRP systems. As for the verification of the proposed model under moisture conditions, predicted pull-out load was compared with the experimental pull-out load. The results showed good agreement for all the FRP systems under investigation.